PEMANFAATAN PPT, MEDIA DIGITAL DAN ARTIFICIAL INTELEGENCE (AI) SERTA TEKNOLOGI DIGITAL LAINNYA PADA PEMBELAJARAN PAI DI SMA NEGERI 10 BANJARMASIN - Rika, Rika; Adawiyah, Rabiatul; Sufiyah, Siti; Cahyadi, Ani (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Monotonous traditional PAI learning is difficult to attract millennial students. SMA Negeri 10 Banjarmasin adopts digital media such as PPT, video and the internet to create interactive and collaborative learning. This approach, in line with constructivism theory, improves student understanding and the relevance of learning in the digital era. From this background, the purpose of this study is to describe the utilization of PowerPoint (PPT), digital media, and Artificial Intelligence (AI) in learning Islamic Religious Education (PAI) at SMA Negeri 10 Banjarmasin. This journal is written based on field research that uses a qualitative approach with descriptive methods, the data collection techniques are interviews, observations, and documentation. The data processing technique has four stages, namely data collection, editing, data classification, and data interpretation. While the data analysis uses the Miles and Huberman Model there are three series of data reduction, data presentation, conclusion drawing and verification. The results showed that the implementation of PAI learning in SMA Negeri 10 Banjarmasin utilizes digital technology such as Canva, Google Classroom, Google Form, AI ChatGPT, and mobile phones to support interactive and creative learning. The use of these technologies increases efficiency, engagement, and student motivation, despite facing challenges such as technology misuse and device limitations. With proper planning and management, this digital-based learning is expected to improve the quality of PAI education according to the vision of Merdeka Curriculum.